2009
DOI: 10.1111/j.1399-5618.2009.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of specific adenylyl cyclase isoforms by lithium and carbamazepine, but not valproate, may be related to their antidepressant effect

Abstract: Lithium and carbamazepine preferentially inhibit AC5, albeit via different mechanisms. Lithium competes with Mg(2+), which is essential for AC activity; carbamazepine competes for AC's catechol-estrogen site. Antidepressant-like behavior of AC5 knockout mice in the forced-swim test supports the notion that AC5 inhibition is involved in the antidepressant effect of lithium and carbamazepine. The effect of lithium and carbamazepine to lower cAMP formation in AC5-rich dopaminergic brain regions suggests that D1-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 82 publications
4
17
0
Order By: Relevance
“…It has been reported that CBZ influences the expression of CYP3A4, ABCB1, DRD1, CYP2C8, HLA-B, PLA2G4A, ABCC2, EPHX1, NR1I2, ESR1, CCND1, CYP2B6, GRIK2, NR3C1, and SLC5A5 [15][16][17][18][19][20][21][22] . The genetic variants in ABCC2, EPHX1, TNF, and HSPA1L that affect susceptibility to CBZ can be used to predict maintenance doses of CBZ 21,23-25 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CBZ influences the expression of CYP3A4, ABCB1, DRD1, CYP2C8, HLA-B, PLA2G4A, ABCC2, EPHX1, NR1I2, ESR1, CCND1, CYP2B6, GRIK2, NR3C1, and SLC5A5 [15][16][17][18][19][20][21][22] . The genetic variants in ABCC2, EPHX1, TNF, and HSPA1L that affect susceptibility to CBZ can be used to predict maintenance doses of CBZ 21,23-25 .…”
Section: Discussionmentioning
confidence: 99%
“…Many putative mechanisms of action of lithium have been proposed . Among them are selective inhibition of specific isoforms of adenylyl cyclase that are associated with antidepressant‐like behaviors in animal models, antagonism at dopamine receptors indirectly through inhibition of GSK 3 enzyme, and increased serotonin (5‐HT) levels in various brain areas such as dorsal hippocampus and lateral hypothalamus with lithium use . Perhaps, the effect of lithium on normalization of the abnormal circadian rhythm in bipolar patients may be of more interest in explaining why it could plausibly be effective in both CH and HH …”
Section: Treatment Optionsmentioning
confidence: 99%
“…Competition with magnesium for binding sites also modulates actions of lithium on G-protein-mediated cellular signaling transduction pathways (GTP binding and cyclic AMP production) through inhibition of adenylyl cyclase (Ebstein et al, 1976; Ebstein et al, 1978; Andersen and Geisler, 1984; Ebstein et al, 1987; Newman and Belmaker, 1987; Avissar et al, 1988; Mørk and Geisler, 1989; Minadeo et al, 2001; Srinivasan et al, 2004). Lithium selectively inhibits specific isoforms of adenylyl cyclase that are associated with antidepressant-like behaviors in animal models (Mann et al, 2008; Mann et al, 2009). …”
Section: Lithium and Magnesiummentioning
confidence: 99%